2002
DOI: 10.1086/341914
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Microflora Studies in Late‐Onset Autism

Abstract: Some cases of late-onset (regressive) autism may involve abnormal flora because oral vancomycin, which is poorly absorbed, may lead to significant improvement in these children. Fecal flora of children with regressive autism was compared with that of control children, and clostridial counts were higher. The number of clostridial species found in the stools of children with autism was greater than in the stools of control children. Children with autism had 9 species of Clostridium not found in controls, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
410
5
18

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(453 citation statements)
references
References 33 publications
10
410
5
18
Order By: Relevance
“…41 Several studies have now reported changes in microbiota profile in patients with autism. [41][42][43][44][45][46][47] While this area of research is new and consensus across studies has not yet been established, several interesting observations are worth noting. In one recent study, an increased diversity of microbiota was observed in patients with severe autism compared with matched controls; and in particular Bacteroidetes was significantly increased in patients with autism, whereas Firmicutes was observed to be higher in controls.…”
Section: Effects Of the Central And Peripheral Nervous Systems On Thementioning
confidence: 99%
“…41 Several studies have now reported changes in microbiota profile in patients with autism. [41][42][43][44][45][46][47] While this area of research is new and consensus across studies has not yet been established, several interesting observations are worth noting. In one recent study, an increased diversity of microbiota was observed in patients with severe autism compared with matched controls; and in particular Bacteroidetes was significantly increased in patients with autism, whereas Firmicutes was observed to be higher in controls.…”
Section: Effects Of the Central And Peripheral Nervous Systems On Thementioning
confidence: 99%
“…Moreover, Vrieze et al have reported that insulin sensitivity of recipients with metabolic syndrome increased 6 weeks after infusion of intestinal microbiota from lean donors [173]. The therapeutic effects of FMT also can be applicable to other disorders, such as Parkinson's disease [174], chronic fatigue syndrome [175], and childhood regressive autism [176].…”
Section: Fecal Microbiota Transplant (Fmt)mentioning
confidence: 99%
“…Recent researches suggested that gut microbiota modulate the brain function of its host through the gut-brain axis (Turnbull et al, 1999;Finegold et al, 2002;Shanahan, 2002;Sudo et al, 2004;Desbonnet et al, 2008;Neufeld et al, 2011). The series of events in the GI tract following postnatal microbial colonization resulted a long-lasting impact on the neural processing of sensory information regarding the hypothalamic-pituitary-adrenal stress response (Finegold et al, 2002). Early postnatal bacterial colonization in germfree (GF) mice promoted the development of central nervous system (CNS) (Turnbull et al, 1999).…”
Section: The Gut-brain Axis and Brain Functionmentioning
confidence: 99%